Insubordinate Costume. Issue 2 (1st December 2021) - Marshall, Susan
In this visual essay, I explore the way costume can be used as a research tool and how playing with my modular 'Insubordinate Costumes' enables different creative interpretations and offers diverse dramaturgical possibilities. The term 'Insubordinate Costume' evolved from my research and is used to reflect the defiant, rebellious and unruly nature of performance-defining costume, which flouts practicalities and textual confines to embrace the role of protagonist. In order to explore the agency of 'Insubordinate Costume', I developed flat-pack modular costumes, which can be constructed in different ways and organized workshops with both single performers and small groups in order to analyse a range of different approaches to performance making. The rule of play is essential to the approach to these costumes, both in the playful essence of the costume and in the way the body interacts with it. Although the modular pieces are always the same, the resulting sculptural forms created by each performer have always been unique, as have their performances. Looking at New Materialism theories, my practice research can be considered as an assemblage of human and non-human elements, which together have a greater power and the ability to generate a performance.